Kinematic Robutness of Manipulating Systems - Galhano, Alexandra (2019)
Present day mechanical manipulators have poor performances when compared with the human arm. In fact, joint-driven manipulators are not efficient due to the high actuator requirements imposed by the transients of the operational tasks. muscle-actuated arms are superior because the anatomic levers adapt the manipulating exigences to the driving linear actuators. The kinematic analysis of these systems highlights its main properties and constitutes a step towards the design of new mechanical biological-like robotic structures adopting linear actuators replacing the standard rotational joint-driving motor systems.